Changes in Lipoprotein‐Associated Phospholipase A2 Activity Predict Coronary Events and Partly Account for the Treatment Effect of Pravastatin: Results From the Long‐term Intervention with Pravastatin in Ischemic Disease Study. Issue 5 (23rd October 2013) - White, Harvey D.; Simes, John; Stewart, Ralph A. H.; Blankenberg, Stefan; Barnes, Elizabeth H.; Marschner, Ian C.; Thompson, Peter; West, Malcolm; Zeller, Tanja; Colquhoun, David M.; Nestel, Paul; Keech, Anthony C.; et al.
Abstract : Background: Lipoprotein‐associated phospholipase A2 (Lp‐PLA2 ) levels are associated with coronary heart disease (CHD) in healthy individuals and in patients who have had ischemic events. Methods and Results: The Long‐term Intervention with Pravastatin in Ischemic Disease (LIPID) study randomized 9014 patients with cholesterol levels of 4.0 to 7.0 mmol/L to placebo or pravastatin 3 to 36 months after myocardial infarction or unstable angina and showed a reduction in CHD and total mortality. We assessed the value of baseline and change in Lp‐PLA2 activity to predict outcomes over a 6‐year follow‐up, the effect of pravastatin on Lp‐PLA2 levels, and whether pravastatin treatment effect was related to Lp‐PLA2 activity change. Lp‐PLA2 was measured at randomization and 1 year, and levels were grouped as quartiles. The prespecified end point was CHD death or nonfatal myocardial infarction. Baseline Lp‐PLA2 activity was positively associated with CHD events ( P <0.001) but not after adjustment for 23 baseline factors ( P =0.66). In 6518 patients who were event free at 1 year, change in Lp‐PLA2 was a significant independent predictor of subsequent CHD events after adjustment for these risk factors, including LDL cholesterol and LDL cholesterol changes ( P <0.001). Pravastatin reduced Lp‐PLA2 by 16% compared with placebo ( P <0.001). After adjustment for Lp‐PLA2 change, the pravastatin treatment effect was reduced from 23% to 10% ( P =0.26), with 59% of the treatment effect accounted for by changes in Lp‐PLA2 . Similar reductions in treatment effect were seen after adjustment for LDL cholesterol change. Conclusion: Reduction in Lp‐PLA2 activity during the first year was a highly significant predictor of CHD events, independent of change in LDL cholesterol, and may account for over half of the benefits of pravastatin in the LIPID study.